Timor-Leste : Country Environmental Analysis - World Bank (Washington, DC, 2017)
The Country Environmental Analysis (CEA) for Timor-Leste identifies environmental priorities through a systematic review of environmental issues in natural resources management and environmental health in the context of the country's economic development and environmental institutions. Lack of data has been the main limitation in presenting a more rigorous analysis. Nevertheless, the report builds on the best available secondary data, presents new data on the country's wealth composition, and derives new results on the costs of water and air pollution. The CEA calls for urgent attention to gaps in the environmental management framework, the lack of capacity to implement the few regulations in place, and the high cost of indoor air pollution and poor water, sanitation, and hygiene. Timor-Leste is a young country that regained independence in 2002, and it has emerged from a bitter past burdened by colonialism and violent conflicts. It is still a fragile state facing enormous challenges. The report also points out the lack of clean water, appropriate sanitation, and hygiene as an environmental priority. The CEA estimates that this imposes an economic cost of about $17 million per year by way of illness and premature death. The CEA also looks at outdoor air pollution and at natural resource management for land, forestry, and coastal and marine resources. Outdoor air pollution is not a serious problem for the time being, but it could become so in the long run if the economy grows rapidly, urbanization continues, heavy industry emerges, and motorization increases rapidly. This underlines the need for good forward territorial and development planning. In conclusion, much good work has already been done to enhance the quality of the environment in Timor-Leste. Efforts are under way to improve the data base for environmental management.